Transition Metal‐Catalyzed Dicarbofunctionalization of Unactivated Olefins - Dhungana, Roshan K.; KC, Shekhar; Basnet, Prakash; Giri, Ramesh (Chemical record, 2018)
Transition metal (TM)‐catalyzed difunctionalization of unactivated olefins with two carbon‐based entities is a powerful method to construct complex molecular architectures rapidly from simple and readily available feedstock chemicals. While dicarbofunctionalization of unactivated olefins has a long history typically with the use of either carbon monoxide to intercept C(sp3)‐[M] (alkyl‐TM) species or substrates lacking in β‐hydrogen (β‐Hs), development of this class of reaction still remains seriously limited due to complications of β‐H elimination arising from the in situ‐generated C(sp3)‐[M] intermediates. Over the years, different approaches have been harnessed to suppress β‐H elimination, which have led to the development of various types of olefin dicarbofunctionalization reactions even in substrates that generate C(sp3)‐[M] intermediates bearing β‐Hs with a wide range of electrophiles and nucleophiles. In this review, these developments will be discussed both through the lens of historical perspectives as well as the strategies scrutinized over the years to address the issue of β‐H elimination. However, this review article by no means is designed to be exhaustive in the field, and is merely presented to provide the readers an overview of the key reaction developments. Various transition metal‐catalyzed dicarbofunctionalization reactions of olefins are described. These reactions are conducted with transition metals such as Ti, Cr, Mn, Fe, Co, Ni, Cu, Rh and Pd, and are performed both intra‐ and intermolecularly in two‐, three‐ and multi‐component manners to contruct complex carbon skeletons from simple and readily available feedstock chemicals.